2016
DOI: 10.1253/circj.cj-16-0193
|View full text |Cite
|
Sign up to set email alerts
|

New Stethoscope With Extensible Diaphragm

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp (Figure A, Left). The EPDM diaphragm is firmly fixed and the force is extended by tightening a lid with a spiral groove, which lifts the center by 1 mm, thus increasing the vibration of the plastic plate, and so the sound volume also increases. The comparative structure of the SDS and EDS is shown in Figure A, Right.As a preliminary test, 2 of the authors investigated the acoustic characteristics of various stetho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Thereafter, sound waves are propagated via the hollow tubing to the binaural earpiece, providing audio output to both ears [14][15][16]. Takashina et al also found that adding an ethylene propylene diene monomer as an extensible diaphragm increases the efficiency of sound analysis [17].…”
Section: Analogue Stethoscopementioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, sound waves are propagated via the hollow tubing to the binaural earpiece, providing audio output to both ears [14][15][16]. Takashina et al also found that adding an ethylene propylene diene monomer as an extensible diaphragm increases the efficiency of sound analysis [17].…”
Section: Analogue Stethoscopementioning
confidence: 99%
“…There are also many other benefits to the use of digital stethoscopes in an educational setting. A cardiology patient simulator developed through the application of new digital computer technology is capable of playing back selected physical findings such as cardiac and respiratory sounds that have been pre-recorded from actual patients using digital stethoscopes, and can be configured to a loudspeaker, enabling multiple listeners to listen to the same internal body sounds simultaneously, with on-demand playback [17]. The signal can also be graphically represented on spectrograms, which serve as a visual aid to augment the teaching of auscultation, and also allow analysts to ascribe visual correlations to the exceptionally low-frequency components of cardiac sounds [2,22].…”
Section: Digital Stethoscopementioning
confidence: 99%
“…Since Laennec invented the first stethoscope based on the acoustic characteristics of the pipeline in 1816, the acquisition technology had been constantly updated [3]. Traditional stethoscopes were difficult to cope with the interference of ambient noise, and the accuracy of diagnosis was influenced by the experience and ability of the physician [4].…”
Section: Introductionmentioning
confidence: 99%